Panorama actual y perspectiva futura sobre los efectos del covid-19 en la comercializadora Agricola Productiva y Asociados PRODUCTIVACORP S.A. mediante la comparación de los estados financieros de los años 2019 – 2020 - Laje Montoya, Cristian Alexi (2021)
This case study focuses on the analysis and interpretation of comparative charts of the sales of the company Comercializadora Agrícola Productiva & Asociados Productivacorp S.A. with R.U.C. 1291760712001., from fiscal years 2019 and 2020, a company dedicated to the activity of managing irrigation systems for agricultural purposes, as well as the wholesale of chemical products for agricultural use. It is intended to apply the analysis methods that are useful in decision making, for this study the nature of the company will be briefly presented, the theoretical foundations used in the analysis and development of this study.